Pesantren sebagai Solusi dalam Mengatasi ‘Maniak’ Media Sosial dan Game Anak: Studi Kasus Santri di Pondok Pesantren An-Nur Bantul Yogyakarta - Muhammad Adam Fikri (Musala : Jurnal Pesantren dan Kebudayaan Islam Nusantara, 2022)
This research aims to find out how Islamic boarding schools were used as a solution to overcoming social media maniacs and games for students at Pondok Pesantren An-Nur Bantul Yogyakarta. This research method used a descriptive approach. The data used include primary and secondary data. The research results showed that Islamic boarding schools were not just places to seek knowledge. But on the other hand, this pesantren also educated its students in matters of ethics, etiquette and manners. With various efforts and approaches, this pesantren had proven to be able to break up children who became addicted to gadgets, especially social media and games. The An-Nur Islamic Boarding School in Bantul Yogyakarta also faced various problems or challenges. The state of the world was increasingly advanced and developing if students did not follow it, makes it lack external knowledge, were less capable in terms of technology, lack confidence, and some even did not want to follow technological developments. Therefore, these pesantren needed direction and guidance from various related parties so that these problems could be resolved.